A Strategic Plan for Academic Improvement (PEMA). Case Study to Determine the Improvement of Linguistic Competence of Students in the English Major (Revista Espiga, 2019)
A Strategic Plan for Academic Improvement (PEMA) was implemented for students to develop their linguistic and academic competence in the English Teaching Major for I and II Cycles at Universidad Estatal a Distancia (UNED). The 24-week personalized online course provided students with extra linguistic practice, focusing on their specific needs. Tutors designed lessons based on the students’ weaknesses, worked on their skills weekly, and gave them feedback after each session. Students created a portfolio with self-assigned exercises and also shared their challenges, feelings and expectations with their teachers. Even when the students’ language development in the 4 macro skills was not linear because of the complexity of language learning, both students and teachers reported that PEMA helped them perform better in different academic tasks.
Keywords: Second Language acquisition; English as a Foreign Language; Distance education; Online tutoring; Linguistic competence; Academic improvement